(untitled) (Medical Forum Monthly, 2024)
ABSTRACT Objective: To determine the frequency of hypoglycemic episodes among cirrhotic patients presenting to tertiary care hospital. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the Department of Medicine, Khyber Teaching Hospital from May, 2017 to October, 2017. Materials and Methods: 150 male and female cirrhotic patients aged between 18 and 65 years, and fulfilling the inclusion criteria were recruited in the study. Patients were stratified into different grades of hepatic encephalopathy according to West Haven criteria. A random blood sugar level of 72mg/dl was taken as cut off level. Those presenting with levels less than 72mg/dl were labeled as having hypoglycemia. Data collected were entered in SPSS 23. Mean ± SD were calculated for continuous variables and categorical variables were expressed as frequencies and percentages. Effect modifiers were controlled though stratification. Chi square test was used by taking p-value less than or equal to 0.05 as significant for post stratification. Results were presented as tables. Results: A total of 150 patients with hepatic encephalopathy due to liver cirrhosis were included in the study. Male to female ratio was 1.42:1. Average age of the patients was 52.24 years+10 SD. Average blood glucose level in patients with hepatic encephalopathy due to liver cirrhosis was 88 mg/dl+ 6.32 SD. Majority (102 (68%)) of patients had more than or equal to 72mg/dl blood glucose level while 48 (32%) patients had less than 72mg/dl blood glucose level. Majority (48.66%) of the patients presented in Grade II hepatic encephalopathy. Among cirrhotic patients with hepatic encephalopathy that presented with hypoglycemia, 4 were aged <30 years, 10 were aged between 31 and 45 years, 26 were aged between 46 and 60 years and 8 were aged >60 years. 34.17% male and 29.57% female patients developed hypoglycemia. Slightly more hypoglycemic episodes were seen among patients with higher grades of encephalopathy Conclusion: Hypoglycemia is seen among patients with hepatic encephalopathy due to liver cirrhosis. It is not yet clear whether hypoglycemia is jointly responsible for the increased short-term mortality of patients with hepatic encephalopathy due to liver cirrhosis or is only a consequence of the severity of the disease or the complications. Further multi-centered trials are recommended to prove this relationship.